Effect of oil-enriched tomato powder and simvastatin on yolk cholesterol and color in laying hens (Journal of Advanced Veterinary and Animal Research, 2026)
Objective: This study was conducted to investigate the influence of varying levels of oil-enriched tomato powder (OTP) and simvastatin supplementation on the performance and egg quality of laying hens. Materials and Methods: Two hundred 32-week-old Lohmann–Brown hens were utilized in this study and divided into five groups: T1 = control diet; T2 = control diet + 0.03% simvastatin; T3 = 6% OTP in diet; T4 = 12% OTP in diet; and T5 = 18% OTP in diet. Results: The treatments with different levels of OTP and simvastatin had no significant effect on the performance of laying hens (p > 0.05), including egg weight, egg mass, hen-day egg production (HDEP), feed intake, and feed conversion ratio. However, dietary OTP at T5 significantly enhanced the yolk color index (p < 0.05) compared with treatments T1, T2, T3, and T4. Dietary OTP in T5 and supplementation of simvastatin at T2 significantly reduced (p < 0.05) cholesterol level in egg yolk, with the lowest cholesterol level produced by treatment T2. Conclusion: Dietary inclusion of 18% OTP in the diet improves yolk color index and reduces cholesterol without affecting laying hen performance, though simvastatin is more effective in cholesterol reduction.J. Adv. Vet. Anim. Res., 12(4): 1396 -1404, December 2025http://doi.org/10.5455/javar.2025.l999